Technical note: Correlation between TQA data trends and TomoHD functional status. (6th March 2014) - Choi, Hervé H.F.; Ho, Joan P.Y.; Yang, Bin; Cheung, Kin Yin; Yu, Siu Ki
Abstract : TomoTherapy Quality Assurance (TQA) is a software package developed to monitor certain aspects of machine performance. In this study, the TQA quantities or data trends most effective in monitoring energy drifts and magnetron stability were determined respectively. This retrospective study used data collected from three TomoHD units. The TQA modules investigated were Step‐Wedge Helical, Step‐Wedge Static, and Basic Dosimetry. First, the TQA quantities correlated with energy changes ( | r | > 0.85, where r is the Pearson's correlation coefficient) were found. The corresponding sensitivities to percentage depth dose (PDD) ratio changes were then calculated and compared. Second, the pulse‐by‐pulse dose stability was compared before and after each magnetron replacement using a nonparametric comparison test (Welch's t‐test), and the raw dose profiles were surveyed. In this study, exit detector flatness obtained in Basic Dosimetry was shown to be the most sensitive ( r = 0.945 ) to energy changes, followed by the energy differences in Step‐Wedge Static ( r = 0.942 ) and Step‐Wedge Helical ( r = 0.898 ) . The three quantities could detect a PDD ratio change of 5.1 × 10 − 4, 5.4 × 10 − 4, and 7.1 × 10 − 4, respectively. Pulse‐by‐Pulse Dose1 from Basic Dosimetry over a one‐week period before and after a magnetron replacement showed a significant difference ( p < 0.05 ) in only three of the nine instances. On the other hand, a raw output profile free from discontinuities, frequent dropped pulses and abnormal spikes was found to indicate that the magnetron would continue to function normally for a week 89% of the time. PACS numbers: 87.56.bd, 87.56.Fc, 84.40.Fe